(untitled) (Global Journal of Science Frontier Research, 2017)
Density, viscosity and speed of sound of aqueous solution of polyvinyl alcohol of different concentration range from 0.3% to 1% have been measured using ultrasonic interferometer at 1MHz frequency in temperature range 30 0 C-65 0 C. Using these values different acoustical parameters like adiabatic compressibility, acoustic impedance and have been calculated.